Pengaruh Kualitas Pelayanan Dan Nilai Pelanggan Terhadap Kepuasan Anggota Koperasi - Aristyana, Ni Putu Della; Adisti Abiyoga Wulandari, Ni Luh; Sasmita Dewi, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
The purpose of this study was to determine how the influence of service quality and customer value on member satisfaction either partially or simultaneously. This research was conducted at KSP Putra Jaya Mandiri. The number of samples taken was 60 respondents. Data collection techniques are observation, interviews, documentation, literature and questionnaires. While the data analysis techniques are validity, reliability, classic assumption test, multiple linear regression analysis, multiple correlation, t test (t test), determination, and f test (f test). The test results show that there is a positive and significant influence between service quality on member satisfaction, which is seen from the t-test results obtained by t1-count is 3.389 greater than the t-table of 1.671 and a sig value of 0.001. There is a positive and significant influence between customer value on member satisfaction. It can be seen from the t-test results that the t-test is 4.254, which is greater than the t-table of 1.671 and the sig value of 0.000. There is a positive and significant influence between service quality and customer value on member satisfaction as seen from the F-count is 44.303 which is greater than the F-table of 3.15..